Synthetic routes to bicyclo[1.1.1]pentylamines: booming toolkits for drug design. Issue 13 (16th June 2022) - Yu, Zhiyou; Shi, Lei
Abstract : With the flourishing progress of modern medicinal chemistry, bicyclo[1.1.1]pentylamines (BCPAs) have come to the fore as bioisosteres of arylamine motifs to reduce the concern about the risks of arylamines in bioactivity. Abstract : With the flourishing progress of modern medicinal chemistry, bicyclo[1.1.1]pentylamines (BCPAs) have come to the fore as bioisosteres of arylamine motifs to reduce the growing concern about the risks of arylamines related to metabolism, bioavailability, and excretion. In light of the prevalence and significance of BCPAs, an increasing number of new practical protocols to efficiently furnish these appealing molecules have been thus disclosed, which serve to shorten the long synthetic sequences or enable gram-scale syntheses through one-pot multicomponent processes, creating a novel chemical space and systematically streamlining drug design routes.